Mechanical Reinforcement of Proteins with Polymer Conjugation - DeBenedictis, Elizabeth P; Hamed, Elham; Keten, Sinan (ACS nano, 2016)
Conjugating poly(ethylene glycol) (PEG) to peptides, also known as PEGylation, is proven to increase the thermodynamical stability of peptides, and has been successfully applied to prolong the lifetime of peptide-based vaccines and therapeutic agents. While it is known that protein structure and function can be altered by mechanical stress, whether PEGylation can reinforce proteins against mechanical unfolding remains to be ascertained. Here, we illustrate that PEGylation prolongs the lifetime of α-helices subject to constant stress. PEGylation is found to increase the unfolding time through two mechanisms. We see that (1) the unfolding rate of a helical segment is decreased through prolonged plateau regimes where the peptide helical content remains constant, and (2) the proportion of refolding to unfolding is increased, primarily by shielding water molecules from replacing forcibly exposed backbone hydrogen bonds near the conjugation site. Our findings demonstrate the feasibility of improving peptide mechanical stability with polymer conjugation. This provides a basis for future studies on optimizing conjugation location and chemistry to build custom biomolecules with unforeseen mechanical functions and stability.